La adquisición de oposiciones en bilingües castellano–quechua y quechua–castellano - Pérez Silva, Jorge Iván (2017)
De Saussure’s idea that phonological systems are based on distinctive oppositions crystalizes in the work of Jakobson and his collaborators with the “dichotomous scale” of distinctive features. For these scholars, the way a language works, as well as the way it is acquired and lost, depends on the hierarchical organization of the distinctive features. The work of Dresher and his collaborators recovers the importance of this fundamental conception of phonological systems, with the name “contrastive hierarchy”. In this paper, I show that the acquisition of the Spanish vocalic system by Quechua speakers and of the Quechua vocalic system by Spanish speakers amounts to the acquisition of L2 oppositions on the basis of L1 oppositions.